Understanding popular violence in the English Revolution : the Colchester plunderers - Walter, John, 1948- (Past and present publications., 1999)
This book makes an original contribution to the history of the English Revolution and to the meaning of crowd behavior. It recreates one of the most famous episodes, in which crowds from Essex and Suffolk attacked and plundered the houses of the gentry, and sought to ""ethnically cleanse"" their communities of Catholics. The deeper perspective offered by history shows that this action was not ""blind violence"": the book deciphers the logic that informed the crowd's behavior, and finds evidence of both the importance - and reach - of puritanism and popular parliamentarianism